2013
DOI: 10.1016/j.apsusc.2013.06.093
|View full text |Cite
|
Sign up to set email alerts
|

Towards the controlled release of metal nanoparticles from biomaterials: Physico-chemical, morphological and bioactivity features of Cu-containing sol–gel glasses

Abstract: AAM) is copyrighted and published by Elsevier. It is posted here by agreement between Elsevier and the University of Turin. Changes resulting from the publishing process -such as editing, corrections, structural formatting, and other quality control mechanisms -may not be reflected in this version of the text. The definitive version of the text was subsequently published in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 45 publications
3
16
0
Order By: Relevance
“…The different release profile and higher release of Cu + 2 than Zn + 2 ions from either pure doped glass particles or composite scaffolds are due to their differences in atomic radii and electronegativities generating diverse interactions with the nonbridging oxygen of the silicate tetrahedrons from the glass network . Indeed, while Zn can strongly bind to the silicate network forming tetrahedral structures similar as Si atoms hindering its release, no evidence of CuOSi or other connections of Cu to the glass network have been found . The weaker bond of Cu within the glass structure can explain its higher release as compared with Zn ions.…”
Section: Discussionmentioning
confidence: 99%
“…The different release profile and higher release of Cu + 2 than Zn + 2 ions from either pure doped glass particles or composite scaffolds are due to their differences in atomic radii and electronegativities generating diverse interactions with the nonbridging oxygen of the silicate tetrahedrons from the glass network . Indeed, while Zn can strongly bind to the silicate network forming tetrahedral structures similar as Si atoms hindering its release, no evidence of CuOSi or other connections of Cu to the glass network have been found . The weaker bond of Cu within the glass structure can explain its higher release as compared with Zn ions.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of Cu in the 58S glass decreased the ability to form surface crystalline apatites for all percentages of metal incorporated (figure 5(a)) as concluded by the lower intensity of the HA peaks after immersion in SBF. The competition between Cu +2 and Ca +2 ions in solution for the precipitation of phosphate species can explain the lower bioactivity of the doped glasses [25,35]. For the incorporation of Cu in the NaBG glass ( figure 5(b)) otherwise did not significantly affected the formation of HA.…”
Section: Apatite-forming Ability and Dissolution After Soaking In Sbfmentioning
confidence: 98%
“…By introducing Cu in the glass structure, one can obtain materials with angiogenesis response and with antibacterial activity. The presence of Cu metal as Cu n + species on surface of the glass can be also used to bind different biomolecules in order to obtain drug delivery systems [ 121 ].…”
Section: Metallic Nanoparticles In Composites With Bioactive Glassmentioning
confidence: 99%
“…Several studies revealed that CuNPs containing silicate glasses did not show any bioactivity alteration [ 120 , 121 , 122 ]. The antibacterial activity of silicate glass with Cu has been demonstrated by Popescu et al [ 122 ] by obtaining samples with good antibacterial effects against Staphylococcus aureus .…”
Section: Metallic Nanoparticles In Composites With Bioactive Glassmentioning
confidence: 99%